Make thrift mend : stitch, patch, darn, plant-dye & love your wardrobe - Rodabaugh, Katrina (Abrams, 2021)
Slow fashion influencer Katrina Rodabaugh follows her bestselling book, Mending Matters, with a comprehensive guide to building (and keeping) a wardrobe that matters. Whether you want to repair your go-to jeans, refresh a favorite garment, thrift-shop like a pro, or dye, tailor, and reinvent clothing you already have--this book has all the know-how you'll need. Woven throughout are stories, essays, and a slow fashion call-to-action, encouraging readers to get involved or deepen their commitment to changing the destructive habit of overconsumption. Rodabaugh has an engaged fan group (her kits and classes routinely sell out the first day) and a proven ability to tempt sewists and nonsewists alike to take up needle and thread.